Employing Television Programs in Spreading Environmental Awareness, through Implementation on Estidama Program in Emirate T.V July to October 2018 - Abdelgdir Ali Elfaki, Fakhri (International Journal of Psychosocial Rehabilitation, 2020)
The various functions of television programs are important information functions that enable it to play its role as a community-based media service, and the function of educational television programs plays a major role in promoting environmental awareness and raising awareness of the most important environmental issues . In this study the researcher has tackled employing TV programs in spreading awareness of environmental issues through implementation on the Estidama program on Emirate TV so as to introduce the experiment of the program, to realize its effect, to assume the role of prevailing environmental awareness, and to get acquainted with the characteristics of UAE environmental features, for it is one of the advanced countries. The researcher also has tried to find solutions to environmental problems and challenges, to know the role of visual media, and to employ digital technologies in achieving environmental sustainability. In this study, the researcher has used the descriptive approach using the survey approach by distributing the questionnaire to a number of media and experts to learn about the nature of the program and to collect, classify, and analyze data in the survey.